The Effect of Diversity Inclusion and Leadership Development Mediation of Digital HR Planning on the Performance of Employees of Bhakti Husada Hospital Banyuwangi - Handy Kurniawan; Trias Setyowati; Riyanto Setiawan Suharsono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Bhakti Husada Banyuwangi Hospital as a multiethnic private hospital faces employee performance challenges due to diversity dynamics and adaptive leadership needs in the midst of human resource digital transformation. This study examines the influence of diversity, inclusion, and leadership development on employee performance with digital HR planning as an intervening variable. Using a quantitative explanatory design approach with a saturated sample of the entire population of 195 medical-non-medical employees, data was collected through a valid questionnaire and analyzed by SmartPLS-based Structural Equation Modeling (SEM). The results showed that diversity inclusion had a positive effect on performance through Java-Madura-local representation and inclusion index; leadership development has a positive effect through IDP-360 feedback of the head of space; both significantly affect digital HR planning; digital HR planning itself improves performance through predictive staffing and succession analytics. The effect of partial mediation was confirmed with the moderate category. These findings enrich the Resource-Based View (RBV) theory in the context of Banyuwangi hospitals, recommending DEI-Leadership Digital HRIS for the optimization of inclusive health human resources